Major Eye Diseases and Risk Factors Associated with Systemic Hypertension in an Adult Chinese Population: The Beijing Eye Study - SHUANG WANG; LIANG XU; JONAS, Jost B; WONG, Tien Y; TONGTONG CUI; YIBIN LI; YA XING WANG; QI SHENG YOU; HUA YANG; CONG SUN (Ophthalmology (Rochester, Minn.), 2009)
To assess the relationship of hypertension with major eye diseases and other ocular parameters. Population-based study. The Beijing Eye Study is a population-based study that included 4439 Chinese subjects examined at the baseline examination in 2001; there was a follow-up examination in 2006, in which 3251 subjects participated, of whom 3222 had blood pressure measurements. All participants underwent an ophthalmic examination, anthropometric measurements, and blood pressure measurement. Hypertension was defined as a systolic blood pressure >or=140 mmHg and/or diastolic blood pressure >or=90 mmHg, and/or self-reported current treatment for hypertension with antihypertensive medication. Blood pressure and ocular parameters, including intraocular pressure and prevalence of major ophthalmic diseases. Mean age of participants in the present study was 60.4+/-10.0 years. Hypertension was present in 1500 (46.6%) of the 3222 subjects who had their blood pressure measured. In multiple regression analysis, hypertension was associated with higher intraocular pressure (beta = 0.39; 95% confidence interval [CI], 0.12-0.66; P = 0.005), focal arteriolar narrowing (odds ratio [OR], 1.78; 95% CI, 1.34-2.36; P<0.001), arteriovenous nicking (OR, 1.50; 95% CI, 1.11-2.04; P = 0.009), generalized retinal arteriolar narrowing (OR, 1.65; 95% CI, 1.30-2.09; P<0.001), retinal vein occlusions (OR, 2.86; 95% CI, 1.21-6.80; P = 0.02), and diabetic retinopathy (OR, 1.90; 95% CI, 1.08-3.31; P = 0.02). Hypertension was not significantly associated with the prevalence of open-angle glaucoma (P = 0.19), angle-closure glaucoma (P = 0.15), age-related macular degeneration (AMD) (P = 0.73), nuclear cataract (P = 0.88), posterior subcapsular cataract (P = 0.30), cortical cataract (P = 0.10), or area of alpha zone (P = 0.05) or beta zone of parapapillary atrophy (P = 0.95). In Chinese persons, while controlling for other systemic parameters, hypertension was associated with increased intraocular pressure, retinal microvascular abnormalities, and prevalence of retinal vein occlusion and diabetic retinopathy. Hypertension was not associated significantly with AMD, age-related cataract, or glaucoma.